2014
DOI: 10.1155/2014/145325
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine and Herbal Supplement Interactions

Abstract: Cyclosporine (CyA) is a well-known immunosuppressant with a narrow therapeutic window. Its bioavailability is affected by many other traditional drugs and herbal extracts. Cytochrome P-450 isoenzymes CYP3A4 and CYP3A5 and protein P-glycoprotein (P-gp) are involved in CyA bioavailability. Interactions of CyA with herbal extracts are not well known, but, given their increased concomitant use, it is important to know which extracts, many of which are commonly self-prescribed, can affect CyA blood concentrations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 43 publications
0
30
0
2
Order By: Relevance
“…BBR modulates the expression/activity of some CYP isoenzymes both in vitro and in vivo [10; 11], and this may translate into clinically relevant interactions with some drugs (Table 1): in renal-transplant recipients, BBR markedly increases the blood concentration of cyclosporine A, due to the inhibition of CYP3A4 and P-gp [12]. An interaction between tacrolimus and BBR, M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 both substrates of CYP3A4-A5, has been reported, resulting in a rapid increase of tacrolimus blood concentration [13].…”
Section: Berberine Absorption and Metabolismmentioning
confidence: 99%
“…BBR modulates the expression/activity of some CYP isoenzymes both in vitro and in vivo [10; 11], and this may translate into clinically relevant interactions with some drugs (Table 1): in renal-transplant recipients, BBR markedly increases the blood concentration of cyclosporine A, due to the inhibition of CYP3A4 and P-gp [12]. An interaction between tacrolimus and BBR, M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 both substrates of CYP3A4-A5, has been reported, resulting in a rapid increase of tacrolimus blood concentration [13].…”
Section: Berberine Absorption and Metabolismmentioning
confidence: 99%
“…Dėl to jonažolių negalima skirti kartu su antidepresantais, priklausančiais MAO inhibitorių ir SSRI grupėms [29]. Be to, prieš skiriant jonažoles reikia įsitikinti, ar pacientas kartu nevartos kitų serotoninerginiu poveikiu pasižyminčių ir citochromo P450 3A4 poveikį keičiančių vaistų, nes iki šiol nėra pakankamai ištir-ta, su kokiais vaistais jonažolės gali turėti kliniškai reikšmin-gų sąveikų [30][31][32][33][34].…”
Section: Diskusijaunclassified
“…It has been reported that St John's wort, ginger, liquorice, scutellariae radix and quercetin decrease CsA levels [126]. Increased CsA levels observed frequently by grapefruit juice consumption [126,127], and also with chamomile, berberine, cannabidiol and resveratrol. Generally, these and some other products suspicious for interactions should be avoided in concomitant use [126].…”
Section: Interactionsmentioning
confidence: 99%